Dominanta semantyczna gatunku mowy (na przykładzie negacji w skargach potocznych) - Wyrwas, Katarzyna (Stylistyka, 2006)
In the article author presents some remarks about genres dominants which can be structural and semantic «..nd. Text structural dominant .s usually possible to reconstruct, constant construction pattern. Semantic dominant is not so easy to find because it? in[1]dexes are not shown on the text surface - they may often be hidden in semantic structure of words. Spoken complaint is the best genre to show semantic dominant because in com[1]plaint speaker expresses the negative emotions and the ubiquitous negation that is conta[1]ined in words or in they semantic structure, in spoken compli mts there are plenty of nega[1]tive pron"uns and particles, many contrasting syntactic constructions, comparisons and exclamations with negative character, rhetorical questions, antonyms and repetition of negative characterized words.